Sistem Informasi Kontrol Stock Barang Berbasis Web Menggunakan Metode RAD (Rapid Application Development) (Studi Kasus : Toko Mutiara) - Ari Prasetya; Maulana Ardhiansyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Information technology is an important need in advancing the company, a variety of information technology can be used for work purposes, one of which is a website-based application. As in the sales business, technology can be used as a tool in the work process, such as managing stock control of goods. Information systems for stock control This item is a web-based system to help the pearl shop business process. This study discusses the Web-Based stock control information system using the RAD (Rapid Application Development) method and this is made to facilitate pearl shop owners in terms of data collection and report management. The results of this study are a web-based inventory control information system that can help the store in the service process in order to find out how much stock of goods is left and can be reused. It is hoped that in the future this application can be developed so that it can be run on different platforms.